Data Mining dalam Mengidentifikasi Calon Penerima Bantuan Satu Keluarga Satu Sarjana (SKSS) dengan Menggunakan Algoritma K-Means - Mustopa Husein Lubis; Febrianti, Wenti (Jurnal Informatika Ekonomi Bisnis, 2022)
Regional Regulation (PERDA) of Dharmasraya Regency Number 4 of 2009 concerning the Formation and Structuring of Nagari, one of the programs is the One Family One Bachelor (SKSS) assistance provided by the National Amil Zakat Agency (Baznas). This program aims to provide assistance so that the survival of the underprivileged can be overcome. Assistance provided by the government is educational assistance for families who have children during their education but cannot afford it in terms of costs. This One Family One Bachelor (SKSS) assistance is given to every sub-district in Dharmasraya, including Tiumang District which is one of the sub-districts in Dharmasraya Regency, West Sumatra Province. This program is intended to assist poor families in continuing their son's education to college level. Identification of prospective recipients of One Family One Bachelor (SKSS) assistance is obtained after a selection is made based on criteria that are in accordance with what is needed. The purpose of this study was to identify potential recipients of SKSS assistance in Tiumang District, Dharmasraya Regency. This research method uses data testing from Tiumang District, Dharmasraya Regency using the K-Means Cluster algorithm, which is to classify whether or not it is appropriate to receive the assistance. Based on the results of the identification using the K-means cluster, the grouping is feasible and not feasible. The amount of data used is 25 family data. The data used includes the criteria for the amount of parental income, the number of dependents of parents, the average value of the National Examination (UN), and memorizing the Koran. The results of the test showed that the eligible cluster 1 was 8 people, and the inappropriate cluster 2 was 17 people. So this research is very helpful in processing the determination of families who get Zakat to continue higher education